Methodological quality criteria in the final dissertations of the degree in administrative law - Élide Hernández (Universidad Central de Venezuela, 2021)
The purpose of this study was to analyze the content of the final dissertation projects approved and available to the public between 2005 and 2016, corresponding to the Specialization program in Administrative Law of the Faculty of Legal and Political Sciences of the Central University of Venezuela. The analysis was carried out in terms of the methodological quality of its criteria: completeness, coherence, suitability, originality, and relevance. The study was based on analytical research, supported by a mixed design: longitudinal and evolutionary, and univariate and documentary. The units of analysis were made up of the dissertations of the aforementioned program approved in the indicated period. For data collection purposes, a documental review technique was used, and the comprehensive research analysis matrix was applied as an instrument. The data was analyzed by combining qualitative and quantitative techniques. Content analysis allowed the researchers to interpret and search for the meaning of the information, according to the results obtained and expressed in quantitative terms. The quality criteria were present in the dissertations with the following median: suitability 4.66; coherence 2.5; completeness 2.0; relevance and originality 0. Methodological quality obtained a median of 2.50. These results place the criteria and quality in the “very low” category, which shows a low level of methodological quality present in the content of the analyzed dissertations.  Key words: research training; research methodology; methodological quality criteria; research; university